Determining Business Strategies to Increase Sales Using SWOT and QSPM Methods in Furniture Industry - Amarta, Zain; Etruly, Niki; Prasetya, Juliasari; Prakoso, Galih (Spektrum Industri, 2026)
The company under study is a furniture manufacturer that provides various furniture products. Currently, promotional activities are minimal, which necessitates the implementation of effective marketing strategies to promote its products. The aim of this study is to identify appropriate alternative marketing strategies to assess the company’s potential and enhance its capabilities to reach a broader market. The methods used in this research are SWOT and QSPM. Data processing will be conducted using the IFE and EFE matrices. Based on the calculations, the IFE score obtained is 2.894, and the EFE score is 3.0375. According to these scores, the company is positioned in cell II (grow and build). Based on the SWOT and QSPM results, the recommended strategies to enhance marketing are: increasing the number of sales teams to reach a wider market with a score of 10, enhancing promotional activities to expand market reach with a score of 8.1, and participating in exhibitions to introduce products and the company to the public with a score of 8.